Where Do Facts Matter?: The digital paradox in magazines' fact-checking practices. (21st April 2018) - Currie Sivek, Susan; Bloyd-Peshkin, Sharon
Abstract : Print magazines are unique among nonfiction media in their dedication of staff and resources to in-depth, word-by-word verification of stories. Over time, this practice has established magazines' reputation for reliability, helped them retain loyal readers amid a glut of information sources, and protected them from litigation. But during the past decade, websites, mobile platforms, and social media have expanded the types of stories and other content that magazines provide for readers. Doing so has shortened the time between the creation and dissemination of content, challenging and in some cases squeezing out fact-checkers' participation. This study examines the procedures applied to stories in magazines and their non-print platforms, seeking to discern what decisions were made in response to the speed of digital publication, what effects these decisions have had, what lessons have been learned and what changes have been made over time. The results suggest that fact-checking practices for print content remain solidly in place at most magazines, if executed with diminished resources; however, magazine media are also exploring new processes to ensure accuracy and protect their reputations in an accelerated media environment.